2007
DOI: 10.1002/cncr.22400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an inflammation‐based prognostic score in patients with metastatic renal cancer

Abstract: BACKGROUND.Recently, it was shown that an inflammation‐based prognostic score, the Glasgow Prognostic Score (GPS), provides additional prognostic information in patients with advanced cancer. The objective of the current study was to examine the value of the GPS compared with established scoring systems in predicting cancer‐specific survival in patients with metastatic renal cancer.METHODS.One hundred nineteen patients who underwent immunotherapy for metastatic renal cancer were recruited. The Memorial Sloan‐K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 67 publications
(27 reference statements)
7
162
1
4
Order By: Relevance
“…These studies ( Table 2) have demonstrated that the prognostic value of the GPS is independent of tumour stage (all studies) and conventional scoring systems (44) , superior to performance status (39,42) and superior to other markers of the systemic inflammatory response such as leucocyte or lymphocyte counts (39,40,42,44,45) . Having established a scoring system (the GPS) based on the systemic inflammation-driven loss of weight, lean tissue and performance status, it was of interest to examine its relationship with the general biochemical disturbance of patients with advanced cancer (46) .…”
Section: Development Of a Systemic-inflammation-based Scorementioning
confidence: 98%
“…These studies ( Table 2) have demonstrated that the prognostic value of the GPS is independent of tumour stage (all studies) and conventional scoring systems (44) , superior to performance status (39,42) and superior to other markers of the systemic inflammatory response such as leucocyte or lymphocyte counts (39,40,42,44,45) . Having established a scoring system (the GPS) based on the systemic inflammation-driven loss of weight, lean tissue and performance status, it was of interest to examine its relationship with the general biochemical disturbance of patients with advanced cancer (46) .…”
Section: Development Of a Systemic-inflammation-based Scorementioning
confidence: 98%
“…60 Although the response rate itself is not considered a good surrogate for OS in metastatic RCC, 61 CRP is not only a predictive marker for response, but also a significant prognostic indicator for survival in patients with metastatic RCC. [51][52][53]55,62 In a large Japanese multicenter cohort of 1463 metastatic RCC patients, 62 CRP had significant prognostic impact on OS, as well as time from initial visit to metastasis, Eastern Cooperative Oncology Group Performance Status, serum lactate dehydrogenase and Ca level, all of which were included in the MSKCC criteria. 63 The 1-year OS rate of 598 patients with elevated CRP levels (>3 mg/L) was 55%, compared with 84.7% of 266 patients without those.…”
Section: Prognostic Value Of Crp In Renal Cell Carcinomamentioning
confidence: 99%
“…Two prognostic algorithms have been developed for application to metastatic RCC: the MRCCPS 54 and the GPS. 55 In the GPS, both elevated CRP levels (>10 mg/L) and hypoalbuminemia (<35 g/L) were given a score of 2, whereas either elevated CRP or hypoalbuminemia were given a score of 1. Albumin is a negative acute-phase reactant whose levels decreased under systemic inflammation.…”
Section: Incorporation Of Crp Into Prognostic Algorithms In Rcc Patientsmentioning
confidence: 99%
“…It is now accepted that the host systemic inflammatory response can be assessed by examining the changes in the circulating concentrations of acute-phase proteins, such as elevated concentration of C-reactive protein and low concentrations of albumin (Gabay and Kushner, 1999;McMillan et al, 2001). It is of interest that either singly or combined these factors have been shown to be stage-and performance status-independent prognostic factors in patients with a variety of inoperable cancers (Forrest et al, 2003(Forrest et al, , 2004Al Murri et al, 2006;Crumley et al, 2006;Glen et al, 2006;Ramsey et al, 2007). Similarly, singly these factors have been shown to be tumour stage-independent prognostic factors, prior to surgery, in patients with a variety of primary operable cancers including colorectal cancer (Heys et al, 1998;Longo et al, 1998;Nozoe et al, 1998;Longo et al, 2000;Nielsen et al, 2000;McMillan et al, 2003).…”
mentioning
confidence: 99%